2018
DOI: 10.1161/circulationaha.118.034365
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Architecture of Human Coronary and Aortic Atherosclerosis

Abstract: The human arterial proteome can be viewed as a complex network whose architectural features vary considerably as a function of anatomic location and the presence or absence of atherosclerosis. The data suggest important reductions in mitochondrial protein abundance in early atherosclerosis and also identify a subset of plasma proteins that are highly predictive of angiographically defined coronary disease.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 64 publications
5
100
0
Order By: Relevance
“…The number of SDEGs accounts for about one-third of all probesets (Roche: 39%, HUG: 34%). This result is expected because these subtypes are pure cell types and so more distinctive than would be seen with samples from multicellular complex tissues 9,21,22 . We also applied a Bonferroni multiple testing correction and a more stringent pvalue < 0.001; the number of SDEGs account for 10.7% and 2.7% of all probesets in Roche and HUG data sets, respectively (Table S4)…”
Section: Sdegs (Human Immune Cells)mentioning
confidence: 84%
See 1 more Smart Citation
“…The number of SDEGs accounts for about one-third of all probesets (Roche: 39%, HUG: 34%). This result is expected because these subtypes are pure cell types and so more distinctive than would be seen with samples from multicellular complex tissues 9,21,22 . We also applied a Bonferroni multiple testing correction and a more stringent pvalue < 0.001; the number of SDEGs account for 10.7% and 2.7% of all probesets in Roche and HUG data sets, respectively (Table S4)…”
Section: Sdegs (Human Immune Cells)mentioning
confidence: 84%
“…SDEGs play a critical role in molecularly characterizing and identifying tissue or cell subtypes, and facilitating the supervised deconvolution of complex tissues 5,8,9 . However, detecting SDEGs using tissue or cell-specific molecular expression profiles remains a challenging task 10 .…”
Section: Here We Introduce One-versus-everyone Fold Change (Ove-fc) Tmentioning
confidence: 99%
“…While proteomics has been previously performed separately on atherosclerotic plaques (19, 20) or calcified stenotic aortic valves,(21) the proteomes of these diseased cardiovascular tissues have never been directly compared in any species. To identify shared or deviating mechanisms underlying disease pathogenesis in these two tissues, we performed label-free liquid-chromatography-mass spectrometry (LC-MS) on cryogenically-homogenized human atherosclerotic plaques from carotid endarterectomies and calcified aortic valves that had undergone surgical replacement.…”
Section: Resultsmentioning
confidence: 99%
“…The following genes involved in the regulation of various pathways of inflammation, according to various GWAS, are significantly associated with atherosclerotic cardiovascular diseases (CVD): CXCL12, MCP-1, TLRs, SH2B3, HLA, IL-6R, IL-5, PECAM1, and others [70]. In studies based on the proteomics approach, the crucial role of inflammation was also shown by the example of the activation of the TNF-α pathway in the vascular wall, as well as the migration of monocytes into the subendothelial compartment (ANRIL) [71,72].…”
Section: Endotype Associatedmentioning
confidence: 99%